Living Qur'an Approach in the Tradition of Zikir Wirdul Lathif in Raudhatuzzahro Madras Palembang: Dynamics, Meanings, and Receptions in Contemporary Islamic Contexts - Fatimah Amirah; Halimatussa'diyah; Zulfikar, Eko; Muhammad Fadhil (Al-Karim: International Journal of Quranic and Islamic Studies, 2025)
This study examines the tradition of reciting Wirdul Lathif dhikr at Madras Raudhatuzzahro Palembang within the framework of Living Qur’an. The research aims to understand the process of reciting Wirdul Lathif, how it has developed into a tradition, and how the female students (santriwati) perceive and respond to this practice. This study employs a qualitative method with a Living Qur’an approach and a field research design. Data were collected through interviews, observations, and documentation. The findings reveal that the Wirdul Lathif dhikr tradition undergoes an externalization process from teachers to students, followed by objectivation through the teaching of texts, sanad (chain of transmission), and recitation methods, and ultimately internalization by the female students. This process transforms Wirdul Lathif into a collective practice performed every Wednesday before the Asr prayer. Furthermore, the study identifies three types of reception among the female students: exegetical reception (understanding its meaning and theological foundation), aesthetic reception (appreciating the beauty of the recitation), and functional reception (applying it in daily life). Contribution: Theoretically, this study contributes to Living Qur’an research by demonstrating how wirid and dhikr texts are not only memorized and recited but also shape the religious patterns and spirituality of Muslim communities. This study also enriches the understanding of how Qur'anic reception manifests in communal religious practices.